Overweight And Obesity Repercussion In The Postoperative Of Myocardial Revascularization Surgery - Nyagra Ribeiro de Araújo; Raul Amaral de Araújo; Simone Maria Muniz da Silva Bezerra (SciELO, 2014)
This is a descriptive, retrospective study with cross-sectional quantitative approach, which aimed to relate the body mass index with events in the postoperative period of the myocardial revascularization surgery with use of extracorporeal circulation. The data collection period was between April and June/2012. Patients were divided according to the body mass index and classified as without excess of weight, overweight or obese. The data analysis was based on the descriptive statistics. The patients without excess of weight had more complications, especially those related to the lungs. Among overweight and obese individuals, the cardiovascular complications stood out. The obese subjects had the worse prognostic. Obesity and overweight did not have statistically significant association with a higher frequency of postoperative complications, in spite of the occurrence of cardiovascular complications in this group. The patients without excess of weight had higher risks of developing neurological events.